2016
DOI: 10.1002/ieam.1738
|View full text |Cite
|
Sign up to set email alerts
|

Recalibration of the earthworm tier 1 risk assessment of plant protection products

Abstract: In the first step of earthworm risk assessment for plant protection products (PPPs), the risk is assessed by comparing the no-observed effect levels (NOELs) from laboratory reproduction tests with the predicted exposure of the PPP in soil, while applying a trigger value (assessment factor [AF]) to cover uncertainties. If this step indicates a potential risk, field studies are conducted. However, the predicted environmental concentration in soil, which can be calculated, for example, for different soil layers (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…It should also be noted that the coefficient of variance between controls in this study [6,7] slightly exceeded the limit of 30%, but the study is considered to provide supplementary and supportive information on the safety of AMPA to earthworm populations. Applications at the levels of maximum and 5 times the expected field application rate, as demonstrated in the present study, are unlikely to result in effects on field populations of earthworms [30], so the outcome of the risk assessment for earthworm does not change. It should also be noted that given the strong binding of glyphosate and AMPA to clay particles in the soil, most agricultural soils will deplete the relevant matrix from glyphosate much earlier and the amount of biologically active glyphosate is likely to decrease rapidly in these soils.…”
Section: Earthworm Reproductionmentioning
confidence: 52%
“…It should also be noted that the coefficient of variance between controls in this study [6,7] slightly exceeded the limit of 30%, but the study is considered to provide supplementary and supportive information on the safety of AMPA to earthworm populations. Applications at the levels of maximum and 5 times the expected field application rate, as demonstrated in the present study, are unlikely to result in effects on field populations of earthworms [30], so the outcome of the risk assessment for earthworm does not change. It should also be noted that given the strong binding of glyphosate and AMPA to clay particles in the soil, most agricultural soils will deplete the relevant matrix from glyphosate much earlier and the amount of biologically active glyphosate is likely to decrease rapidly in these soils.…”
Section: Earthworm Reproductionmentioning
confidence: 52%
“…The WOE approach integrates two of the three lines of evidence above: soil dissipation and soil toxicity. Toxic exposure ratios, also known as risk quotients, are used to extrapolate standardized test results and exposure estimates to real‐world scenarios (Christl et al, 2016; Ernst et al, 2016). The TER calculation uses the 28‐d EC 10 and divides it by the potential environmental concentration (PEC soil ) (Christl et al, 2016; Ernst et al, 2016; see Supplemental Eq.…”
Section: Methodsmentioning
confidence: 99%
“…The regulatory relevant PECsoil depth for the risk assessment needs to be calibrated in combination with the Tier 1 assessment factor by comparing the Tier 1 risk assessment with the results from field studies. With this approach, Christl et al (2016) showed that a PECsoil calculated for the 0-5 cm soil layer in combination with the assessment factor of 5 (EC, 2009) provides a sufficiently conservative Tier 1 earthworm risk assessment. Bénit et al (2019) measured inhibition of in situ enzyme activities within the mitochondrial respiratory chain in cells of the earthworm species L. terrestris, that is, SCCR (succinate cytochrome c reductase), GCCR (glycerol-3phosphate cytochrome c reductase), and QCCR (quinol cytochrome c reductase).…”
Section: Risk Assessmentmentioning
confidence: 99%